The impact of melatonin supplementation on auditory reaction time during sleep deprivation: A comparative study in college sportsmen - Kumar G, Vinod; W, Vinu; Kumar, Sathish; A. Kabeer, Dilshith (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Sleep deprivation is prevalent among athletes during competitions and is known to impair both motor and mental performance. This study aimed to assess how these performance decrements vary with melatonin supplementation. Sixty college sportsmen were divided into six groups (n=10 each): (a) disturbed sleep deprivation for 48 hours, (b) complete sleep deprivation for 48 hours, (c) disturbed sleep deprivation for 48 hours with melatonin supplementation, (d) complete sleep deprivation for 48 hours with melatonin supplementation, (e) normal sleep with melatonin supplementation, and (f) normal sleep. Melatonin, a hormone secreted by the pineal gland with known sleep-promoting effects, was administered orally at 6 mg for sleep-deprived groups and a placebo for non-supplemented groups. Auditory reaction time was measured using standard procedures. The results indicated that auditory reaction time decreased after 48 hours of disturbed and complete sleep deprivation, with a greater reduction observed in the melatonin supplementation group than in the placebo group. These findings underscore the complex interplay between sleep deprivation, melatonin supplementation, and auditory processing, suggesting that melatonin supplementation may mitigate the negative effects of sleep deprivation on auditory reaction time in athletes.